2021
DOI: 10.1080/2162402x.2021.1897294
|View full text |Cite
|
Sign up to set email alerts
|

Bromodomain protein BRD4 is an epigenetic activator of B7-H6 expression in acute myeloid leukemia

Abstract: B7-H6, a ligand for the NK activating receptor NKp30, has been identified as a biomarker of poor prognosis in several solid cancers. However, little is known about the role of B7-H6 and the mechanisms that control its expression in acute myeloid leukemia (AML). Epigenome modulation, including epigenomic reader dysregulation, is one of the hallmarks of AML. Bromodomain-containing protein 4 (BRD4), the best-known member of the BET family of epigenetic readers, is overexpressed in AML cells and regulates the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…B7H6, a new newly discovered member of the B7 family, has been found in many tumors but not in normal tissues. Moreover, expression of B7H6 in tumors correlates with tumor progression and poor patient survival-except in gastric carcinoma (14)(15)(16)(17)(18)(19)(20)(21)(22). To date, no studies of the clinical significance of B7H6 expression in human PC have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B7H6, a new newly discovered member of the B7 family, has been found in many tumors but not in normal tissues. Moreover, expression of B7H6 in tumors correlates with tumor progression and poor patient survival-except in gastric carcinoma (14)(15)(16)(17)(18)(19)(20)(21)(22). To date, no studies of the clinical significance of B7H6 expression in human PC have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…There are two forms of B7H6-cell-surface B7H6 and soluble B7H6 (sB7H6)-and both have been detected in primary tumors and the tumor microenvironment, including in glioma, neuroblastoma, breast cancer, non-small cell lung cancer, hepatocellular carcinoma, gastric carcinoma, ovarian cancer, leukemia, and lymphoma-though rarely in normal tissues (14)(15)(16)(17)(18)(19)(20)(21)(22). Cell-surface B7H6 associates with cell damage, and it triggers innate immunity when it binds to NKp30 on NK cells (23).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, high co-expression of immune checkpoints in blast cells of AML patients correlated with poor outcome FLT3 mut , RUNX1 mut , or TET2 mut [ 17 ]. Overexpression of B7-H6, a ligand for the NK activating receptor NKp30, is correlated with the clinical characteristics of poor prognosis in some AML patients [ 18 ]. B7-H7 serves as a potential prognostic indicator, associating with tumor immunity in human pan-cancer, including AML [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This checkpoint molecule is a type I membrane protein with a 51 kDa molecular weight and 454 amino acids [18]. By binding to its receptor on natural killer cells (NKp30), this molecule produces cytotoxic chemokines and activates innate immune responses [17,19,20]. Even though the B7H6 is overexpressed in a variety of tumor cells, the expression of this molecule is low or negligible in normal tissues [17,19,20].…”
Section: Introductionmentioning
confidence: 99%